Feasibility of Enhancing Happiness and Resilience Family-Based Program on Depressive Symptoms among Adolescents - ศรีประสาร, ชนกพร; วัชรสินธุ์, จินตนา; เฮงอุดมทรัพย์, ภรภัทร (Journal of The Royal Thai Army Nurses, 2018)
This pilot study examined the feasibility of implementing the Enhancing Happiness and Resilience Family-Based program. Purposive sampling was used to recruit 10 high-school adolescents with mild to moderate depressive symptoms in Kalasin Province, Northeastern, Thailand. Four measures were used to collect data including a demographic data record form, a Thai version of the Center for Epidemiologic Studies Depression Scale, The enhancing happiness and resilience family-based program, and a program evaluation questionnaire. The participants and family members participated in a weekly program for four weeks, 45-60 minutes per week. Descriptive statistics and a nonparametric test were used to analyze the data. Initial results of the pilot study showed that after completing the Enhancing Happiness and Resilience Family-Based program, participants had significantly decreased depressive symptoms. The participants and family members were satisfied with the program’s content and activities. The feasibility of implementing this program to reduce depressive symptoms among adolescents has been supported. Research beyond the pilot study is needed to examine the program under more controlled conditions. It is anticipated that psychiatric-mental health nurses will be able to implement the program for high-school students after further testing.